Laminated body, semiconductor device, and method for manufacturing laminated body
By forming an intermediate layer with crystalline regions and amorphous regions on the crystal substrate and growing a crystal layer with a second metal oxide thereon, the problems of difficulty in suppressing crystal defects and high production costs in the prior art are solved, and low-cost production of crystal layers with high quality corundum structures is achieved.
Patent Information
- Application Number
- CN201980060388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-27
- Filing Date
- 2019-09-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2039-09-09
AI Technical Summary
When the prior art uses the atomization CVD method and the ELO method, it is difficult to fully suppress crystal defects, resulting in difficult to realize crystals with high quality corundum structures, and complicated processes lead to high production costs and insufficient production capacity.
A laminated body structure with an intermediate layer is adopted, wherein the crystalline region composed of the first metal oxide is mixed with the amorphous region, and the crystal layer of the second metal oxide as the main component is grown on the intermediate layer, and this structure effectively prevents the elongation of dislocation defects.
Effective suppression of crystal defects is achieved, high-quality crystal layer with corundum structure is obtained, and production costs are reduced and production efficiency is improved.
Smart Images

Figure CN112771651B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a stacked body having a crystal layer with a corundum type structure, a semiconductor device using the stacked body, and a method for manufacturing the stacked body having a crystal layer with a corundum type structure. Background Art
[0002] As a next-generation switching element that can achieve high withstand voltage, low loss and high heat resistance, semiconductor devices using gallium oxide (α-Ga2O3) with a large band gap have attracted attention and are expected to be used in power semiconductor devices such as inverters and light-receiving and light-emitting elements.
[0003] A method of mist chemical vapor deposition (Mist CVD, hereinafter also referred to as "mist CVD method") has been developed that uses atomized mist raw materials to grow crystals on a substrate. This method can produce gallium oxide (α-Ga2O3) with a corundum structure (Patent Document 1). In this method, a precursor is prepared by dissolving a gallium compound such as gallium acetylacetonate in an acid such as hydrochloric acid, and the precursor is atomized to generate raw material particles. A mixed gas containing the raw material particles and a carrier gas is supplied to the surface of a substrate with a corundum structure such as sapphire, so that the raw material mist reacts, thereby causing a single-oriented gallium oxide film to grow epitaxially on the substrate.
[0004] In such heteroepitaxial growth, crystal defects caused by the lattice mismatch between the substrate material and the thin film material and the quality of the substrate in particular become a problem. As a method for suppressing these crystal defects, ELO (Epitaxial Lateral Overgrowth) is known. In this method, for example, a mask using an amorphous film is formed on the substrate surface, and selective epitaxial growth starting from the partially exposed substrate surface and lateral growth on the mask are performed. The mask is thus used to prevent dislocations or bend dislocations according to the crystal orientation, thereby reducing defects in the epitaxial film. Patent document 2 discloses an example of using SiO2 as a mask and forming an α-Ga2O3 film.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5793732
[0008] Patent Document 2: Japanese Patent Application Publication No. 2016-100592 Summary of the invention
[0009] Technical Problems to be Solved by the Invention
[0010] The mist CVD method disclosed in Patent Document 1 cannot obtain a high-quality corundum-type crystal in which crystal defects are sufficiently suppressed.
[0011] On the other hand, as the selective growth mask used in the ELO method described in the above-mentioned patent document 2, since an amorphous film having a different composition from the epitaxial film is used, a mask is usually formed using another film-making device different from the device for forming the desired epitaxial film. In addition, the patterning of the mask is generally performed by photolithography. Therefore, when the epitaxial growth based on the conventional ELO method is adopted in order to obtain a high-quality crystalline thin film with suppressed crystal defects, the process is complicated, so there is a problem of increasing the throughput or increasing the production cost.
[0012] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a laminated body of a crystal having a high-quality corundum-type structure with sufficiently suppressed crystal defects, and to provide a method for manufacturing a crystal capable of obtaining a high-quality crystal thin film with suppressed crystal defects at low cost.
[0013] Technical means to solve technical problems
[0014] The present invention is made to achieve the above-mentioned purpose. The present invention provides a stacked body comprising: a crystal substrate; an intermediate layer formed on the main surface of the crystal substrate and having a mixture of a crystalline region of a crystalline phase composed of a corundum-type structure with a first metal oxide as the main component and an amorphous region of an amorphous phase; and a crystal layer of a corundum-type structure with a second metal oxide as the main component formed on the intermediate layer.
[0015] In such a laminate, the extension of dislocation defects from the substrate is prevented in the amorphous region of the intermediate layer, and thus a crystal layer with a high-quality corundum-type structure having few defects is provided.
[0016] In this case, the crystal region can be formed into a stacked body of epitaxial growth layers starting from the crystal plane of the crystal substrate.
[0017] Thus, the crystallized region of the intermediate layer becomes a seed crystal, thereby having a high-quality crystal layer having the same crystal orientation as that of the crystal substrate.
[0018] In this case, a stacked body can be produced in which the ratio of the crystal region contained in the intermediate layer is 1% or more in any cross section of the intermediate layer perpendicular to the main surface of the crystal substrate.
[0019] Thus, the intermediate layer more effectively reduces dislocation defects extending from the crystal substrate, and thus has a higher quality crystal layer.
[0020] In this case, a laminated body can be produced in which the ratio of the crystal region contained in the intermediate layer is 4% to 25% in any cross section of the intermediate layer perpendicular to the main surface of the crystal substrate.
[0021] This results in a higher quality crystal layer.
[0022] In this case, a laminated body in which the film thickness of the intermediate layer is 1 nm or more can be obtained.
[0023] As a result, the intermediate layer can more effectively prevent dislocation defects extending from the crystal substrate, and thus has a higher quality crystal layer.
[0024] In this case, a laminated body in which the intermediate layer has a thickness of 10 nm or more can be obtained.
[0025] This results in a higher quality crystal layer.
[0026] In this case, the first metal oxide may be a laminate containing an oxide of any one of aluminum, titanium, vanadium, chromium, iron, gallium, rhodium, indium, and iridium as a main component.
[0027] Alternatively, the second metal oxide may be a laminate containing an oxide of any one of aluminum, titanium, vanadium, chromium, iron, gallium, rhodium, indium, and iridium as a main component.
[0028] Thus, a stacked body having a crystal layer that is excellent in electrical characteristics and suitable for a semiconductor device is formed.
[0029] In this case, a laminated body in which the intermediate layer further contains silicon can be produced.
[0030] Thereby, an intermediate layer capable of forming a high-quality crystal layer can be formed more stably.
[0031] In this case, the concentration of the silicon contained in the intermediate layer can be made into a laminated body of 0.5 at % or more, more preferably 1 at % or more and 10 at % or less.
[0032] This makes it possible to more stably form an intermediate layer in which a crystalline region and an amorphous region are mixed.
[0033] A laminated body further including a stress relaxation layer between the crystal substrate and the intermediate layer can be obtained.
[0034] Thereby, the crystallinity of the crystal region in the intermediate layer is further improved, and the crystallinity of the crystal layer is further improved.
[0035] In this case, a semiconductor device can be manufactured which includes at least a semiconductor layer and an electrode, and includes at least a part of the stacked body as the semiconductor layer.
[0036] This results in a higher performance semiconductor device.
[0037] At this time, a method for manufacturing a stacked body can be provided, which includes the following steps: a step of forming a first mixed gas mixed with an atomized first metal oxide precursor, a carrier gas, and silicon; a step of supplying the first mixed gas to a heated crystal substrate to form an intermediate layer in which a crystalline region of a crystalline phase composed of a corundum-type structure with the first metal oxide as the main component and an amorphous region of an amorphous phase are mixed; a step of forming a second mixed gas mixed with an atomized second metal oxide precursor and a carrier gas; and a step of supplying the second mixed gas to the heated crystal substrate to form a crystalline layer of a corundum-type structure with the second metal oxide as the main component on the intermediate layer.
[0038] According to such a method for producing a laminated body, a high-quality corundum-type crystal layer can be easily formed at low cost without forming a special mask.
[0039] In this case, the method for manufacturing the stacked body may be configured such that, in the step of forming the first mixed gas, the silicon is added while the atomized first metal oxide precursor and the carrier gas are being transported onto the crystal substrate.
[0040] This makes it possible to easily form an intermediate layer in which a crystalline region and an amorphous region exist in a mixed state.
[0041] In this case, the method for producing the laminated body may be such that the silicon is added by conveying the atomized first metal oxide precursor and the carrier gas through a tube made of a silicone resin.
[0042] This makes it possible to more easily form an intermediate layer in which a crystalline region and an amorphous region are mixed.
[0043] In this case, the method for manufacturing the laminated body may be configured such that, in the step of forming the intermediate layer, the supply amount of the first mixed gas is changed.
[0044] Thereby, the ratio of the crystal region in the intermediate layer and the thickness of the intermediate layer can be easily controlled.
[0045] Effects of the Invention
[0046] As described above, according to the present invention, a laminate having a high-quality corundum-type crystal layer with suppressed crystal defects can be provided. In addition, according to the present invention, a laminate having a high-quality corundum-type crystal layer can be easily and inexpensively produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a diagram showing one form of the structure of the laminated body of the present invention.
[0048] Figure 2 This is a diagram showing another form of the structure of the laminated body of the present invention.
[0049] Figure 3 FIG. 1 is a diagram showing an example of a Schottky barrier diode (SBD) of the present invention.
[0050] Figure 4 FIG. 1 is a diagram showing an example of a high electron mobility transistor (HEMT) of the present invention.
[0051] Figure 5 FIG. 1 is a diagram showing an example of a metal oxide semiconductor field effect transistor (MOSFET) according to the present invention.
[0052] Figure 6 FIG. 1 is a diagram showing an example of an insulated gate bipolar transistor (IGBT) of the present invention.
[0053] Figure 7 FIG. 1 is a diagram showing an example of a light emitting diode (LED) according to the present invention.
[0054] Figure 8 This is a diagram showing one form of an atomizing CVD apparatus used in the method for producing a laminated body of the present invention.
[0055] Fig. 9 The diagram shows a TEM image in Examples.
[0056] Fig.10 A diagram showing a TEM image in a comparative example.
[0057] Fig.11 It is a graph showing the silicon concentration distribution in the laminated body in the Example and the comparative example. DETAILED DESCRIPTION
[0058] The present invention is described in detail below, but the present invention is not limited thereto.
[0059] As described above, a high-quality corundum-type crystal in which crystal defects are sufficiently suppressed is sought.
[0060] The inventors of the present application have repeatedly and earnestly studied the above technical problems, and as a result, have found that the following laminated body has a low-defect, high-quality, corundum-type structure crystal layer, thereby completing the present invention. The laminated body comprises: a crystal substrate; an intermediate layer formed on the main surface of the crystal substrate and having a mixture of a crystal region of a crystal phase composed of a corundum-type structure with a first metal oxide as a main component and an amorphous region of an amorphous phase; and a crystal layer of a corundum-type structure with a second metal oxide as a main component formed on the intermediate layer.
[0061] Furthermore, as described above, a method for producing a laminated body is desired, which method can obtain a laminated body having a high-quality corundum-type crystal structure with suppressed crystal defects at low cost.
[0062] The inventor of the present application has repeatedly conducted careful research on the above technical problems, and as a result, it is found that a high-quality crystal film with suppressed crystal defects can be obtained at low cost by the following method for manufacturing a stacked body, thereby completing the present invention. The method for manufacturing a stacked body comprises the following steps: a step of forming a first mixed gas mixed with an atomized first metal oxide precursor, a carrier gas, and silicon; a step of supplying the first mixed gas to a heated crystal substrate to form an intermediate layer in which a crystalline region of a crystalline phase composed of a corundum-type structure with the first metal oxide as the main component and an amorphous region of an amorphous phase are mixed; a step of forming a second mixed gas mixed with an atomized second metal oxide precursor and a carrier gas; and a step of supplying the second mixed gas to the heated crystal substrate to form a crystal layer of a corundum-type structure with the second metal oxide as the main component on the intermediate layer.
[0063] The following description is given with reference to the accompanying drawings.
[0064] Figure 1 The laminated body 100 of the present invention is shown. The laminated body 100 includes: a crystal substrate 101; an intermediate layer 102 formed on the main surface of the crystal substrate 101 and having a crystal region 102a of a crystal phase composed of a corundum structure with a first metal oxide as a main component and an amorphous region 102b of an amorphous phase mixed therein; and a crystal layer 103 of a corundum structure with a second metal oxide as a main component formed on the intermediate layer 102. A plurality of crystal regions 102a are randomly formed in a columnar shape, and an amorphous region 102b is formed so as to fill in between the crystal regions 102a. In addition, the crystal layer 103 is formed by epitaxial growth starting from the crystal region 102a.
[0065] The crystal substrate 101 is not particularly limited as long as it is a substrate containing crystal as a main component, and may be a known substrate. It may be any of an insulating substrate, a conductive substrate, and a semiconductor substrate. In addition, it may be a single crystal substrate or a polycrystalline substrate. From the perspective of quality and cost, for example, a sapphire substrate is preferably used.
[0066] As the sapphire substrate, for example, a c-plane sapphire substrate, an m-plane sapphire substrate, an a-plane sapphire substrate, etc. can be used. In addition, the sapphire substrate may have an off-angle. The off-angle is not particularly limited, but is preferably 0° to 15°. In addition, the thickness of the crystal substrate is not particularly limited, but is preferably about 200 to 800 μm from the perspective of operation or cost.
[0067] The metal elements constituting the first metal oxide and the second metal oxide may be the same or different. In addition, the expression "having the first metal oxide as the main component" means that in addition to the first metal oxide, a dopant or unavoidable impurities may be contained, for example, it means that the first metal oxide is contained by approximately 50% or more. The second metal oxide is also the same.
[0068] Figure 1 1 shows an example in which the intermediate layer 102 is directly formed on the crystal substrate 101, but the intermediate layer may also be formed via other layers formed on the crystal substrate. In particular, when the lattice mismatch between the crystal substrate and the crystal region becomes a problem, a stress relief layer may be provided between the crystal substrate 101 and the intermediate layer 102.
[0069] Figure 2 FIG. 2 shows a laminate 200 provided with a stress relaxation layer 204. Figure 1 The stacked body 100 shown in the figure has a crystal substrate 201, an intermediate layer 202 in which a crystal region 202a and an amorphous region 202b of an amorphous phase are mixed, and a crystal layer 203 formed on the intermediate layer 202. A stress relaxation layer 204 is provided between the crystal substrate 201 and the intermediate layer 202. Thus, the crystallinity of the crystal region 202a in the intermediate layer 202 can be further improved, and as a result, the crystallinity of the crystal layer 203 can be further improved.
[0070] It is preferable to form the stress relaxation layer 204 when, for example, lattice mismatch between the crystal substrate 201 and the crystal region 202a is alleviated. In this case, it is preferable to change the lattice constant of the stress relaxation layer 204 from a value close to or equal to the lattice constant of the crystal substrate 201 to a value close to or equal to the lattice constant of the crystal region 202a continuously or stepwise along the growth direction of the stress relaxation layer 204. For example, when an intermediate layer containing a crystal region of α-Ga2O3 is formed on an Al2O3 substrate, the lattice constant of the stress relaxation layer 204 is preferably changed from a value close to or equal to the lattice constant of the crystal substrate 201 to a value close to or equal to the lattice constant of the crystal region 202a continuously or stepwise. x Ga 1-x )2O3 (0≤x≤1) forms the stress relaxation layer 204 and it is preferred that the x value gradually decreases from the crystal substrate 201 side to the intermediate layer 202 side.
[0071] So far Figure 1 The laminate 100 described in Figure 2 The common matters in the stacked body 200 described in will be described.
[0072] The amorphous regions 102b and 202b in the intermediate layers 102 and 202 have an effect of preventing the extension of dislocation defects and the like, particularly from the crystal substrate. The crystallized regions 102a and 202a function as seed crystals for the crystal layers 103 and 203 .
[0073] In the process of forming the crystal layer 103, 203, in addition to the epitaxial growth starting from the crystalline region 102a, 202a, the crystal growth starting from the crystal nucleus formed on the surface of the amorphous region 102b, 202b of the intermediate layer 102, 202 may also occur. Unlike the epitaxial growth starting from the crystalline region 102a, 202a, the crystal growth starting from the crystal nucleus formed on the surface of the amorphous region 102b, 202b has a random crystal orientation, so in order to form a higher quality crystal layer 103, 203, it is preferable to set the ratio of the amorphous region 102b, 202b to the crystalline region 102a, 202a to an appropriate range. Therefore, in any cross section perpendicular to the main surface of the crystal substrate 101, 201, the ratio of the crystalline region 102a, 202a contained in the intermediate layer 102, 202 is preferably set to 1% or more, and more preferably 4% or more and 25% or less. In addition, the ratio here is based on the area of each region in the cross section.
[0074] By setting the ratio of the crystalline regions 102 a and 202 a contained in the intermediate layers 102 and 202 to be within the above range, it is possible to produce the crystal layers 103 and 203 of higher quality.
[0075] The thickness of the intermediate layers 102 and 202 is preferably 1 nm or more, more preferably 10 nm or more. By setting the thickness of the intermediate layers 102 and 202 to the above range, the effect of preventing the extension of dislocation defects and the like from the crystal substrate can be further improved.
[0076] The intermediate layers 102 and 202 are not particularly limited as long as they are metal oxides that can obtain a corundum-type structure. For example, an oxide containing any one of aluminum, titanium, vanadium, chromium, iron, gallium, rhodium, indium, and iridium as a main component may be used. More specifically, they are Al2O3, Ti2O3, V2O3, Cr2O3, Fe2O3, Ga2O3, Rh2O3, In2O3, and Ir2O3. In addition, when two elements selected from the above metal elements are set as A and B, (A x B 1-x )2O3(0<x<1) or a binary metal oxide represented by (A) when three elements selected from the above metal elements are represented by A, B, and C. x B y C 1-x-y )2O3(0<x<1, 0<y<1) is a ternary metal oxide.
[0077] In addition, the intermediate layer 102, 202 preferably contains silicon. When the intermediate layer 102, 202 contains silicon, the intermediate layer 102, 202 in which the crystal region 102a, 202a and the amorphous region 102b, 202b are mixed can be formed more stably.
[0078] At this time, the silicon concentration is preferably set to 0.5 at% or more, and more preferably 1 at% or more and 10 at% or less. If it is set to 0.5 at% or more, the amorphous regions 102b and 202b can be formed more stably, and if it is set to 10% or less, the crystalline regions 102a and 202a can be formed more stably.
[0079] In addition, it is known that the proportion of oxygen in the intermediate layer 102, 202 is greater than the stoichiometric ratio of the metal oxide forming the intermediate layer 102, 202. Therefore, it is believed that the silicon added to the intermediate layer 102, 202 forms silicon oxide and acts to disturb the crystal structure of the surface of the crystal substrate serving as the base of the intermediate layer, thereby promoting the formation of an amorphous region.
[0080] The crystal layers 103 and 203 are not particularly limited as long as they are metal oxides that can obtain a corundum-type structure. For example, an oxide containing any one of aluminum, titanium, vanadium, chromium, iron, gallium, rhodium, indium, and iridium as a main component may be used. More specifically, they are Al2O3, Ti2O3, V2O3, Cr2O3, Fe2O3, Ga2O3, Rh2O3, In2O3, and Ir2O3. In addition, when two elements selected from the above metal elements are set as A and B, (A x B 1-x )2O3(0<x<1) or a binary metal oxide represented by (A) when three elements selected from the above metal elements are represented by A, B, and C. x B y C 1-x-y )2O3(0<x<1, 0<y<1) is a ternary metal oxide represented by.
[0081] Furthermore, the crystal layers 103 and 203 may have a single layer structure of the above-mentioned metal oxide, or may have a stacked structure of a plurality of crystal films having different compositions, dopants, etc.
[0082] By using the above-mentioned metal oxide as the metal oxide of the intermediate layer 102, 202 or the crystal layer 103, 203, a crystal layer or a stacked body suitable for a semiconductor device can be obtained.
[0083] In addition, the crystal substrates 101, 201, the intermediate layers 102, 202, and the crystal layers 103, 203 in the stacked bodies 100, 200 of the present invention may be doped with impurities that impart conductivity. As the impurities in this case, for example, when the metal oxide contains at least gallium, any one of silicon, germanium, tin, magnesium, and copper or a combination of these metals may be preferably used. The concentration of the impurities added by doping may be appropriately set according to the target final product. For example, it may be set to 1×10 16 cm -3 Above, 8×10 22 cm-3 In addition, the crystal layers 103 and 203 may be formed into a stacked structure of a plurality of crystal layers to which different impurity concentrations are added.
[0084] The crystal layer in the laminate of the present invention has reduced defect density, excellent electrical properties, and is useful in industry. Such a laminate can be applied to semiconductor devices, etc., and can be used in power devices in particular. In addition, the crystal layer formed as a part of the laminate can be used directly in this state (the state of the laminate), and can also be applied to semiconductor devices, etc. after being peeled off from the crystal substrate, etc. by a known method.
[0085] Furthermore, semiconductor devices can be classified into lateral elements (lateral devices) in which electrodes are formed on one side of a semiconductor layer and vertical elements (vertical devices) in which electrodes are respectively provided on the front and back sides of the semiconductor layer, and at least a portion of the laminate of the present invention can be applied to both lateral devices and vertical devices. It is particularly preferred to be applied to vertical devices.
[0086] Examples of the semiconductor device include a Schottky barrier diode (SBD), a metal semiconductor field effect transistor (MESFET), a high electron mobility transistor (HEMT), a metal oxide semiconductor field effect transistor (MOSFET), a junction field effect transistor (JFET), an insulated gate bipolar transistor (IGBT), or a light emitting diode (LED).
[0087] Preferred examples in which the crystal layer obtained from the laminate of the present invention is applied to an n-type semiconductor layer (n+ type semiconductor or n- semiconductor layer, etc.) will be described with reference to the drawings, but the present invention is not limited to these examples.
[0088] In addition, the semiconductor device exemplified below may further include other layers (eg, insulating layers or conductive layers) depending on specifications or purposes, and may also appropriately add or omit intermediate layers or buffer layers.
[0089] Figure 3 The SBD 400 is an example of a Schottky barrier diode (SBD). The SBD 400 includes an n-type semiconductor layer 401 a doped at a relatively low concentration, an n+ type semiconductor layer 401 b doped at a relatively high concentration, a Schottky electrode 402 , and an ohmic electrode 403 .
[0090] The materials of the Schottky electrode 402 and the ohmic electrode 403 can be known electrode materials. Examples of the electrode materials include metals such as aluminum, molybdenum, cobalt, zirconium, tin, niobium, iron, chromium, tantalum, titanium, gold, platinum, vanadium, manganese, nickel, copper, hafnium, tungsten, iridium, zinc, indium, palladium, neodymium or silver, or alloys of these metals; metal oxide conductive films such as tin oxide, zinc oxide, rhenium oxide, indium oxide, indium tin oxide (ITO), indium zinc oxide (IZO), etc.; organic conductive compounds such as polyaniline, polythiophene or polypyrrole; or mixtures of these components and stacks thereof.
[0091] The Schottky electrode 402 and the ohmic electrode 403 can be formed by, for example, a known method such as a vacuum evaporation method or a sputtering method. More specifically, when the Schottky electrode is formed using a first metal and a second metal of two of the above metals, the Schottky electrode can be formed by stacking a layer formed by the first metal and a layer formed by the second metal, and patterning the layer formed by the first metal and the layer formed by the second metal using a photolithography technique.
[0092] When a reverse bias is applied to the SBD 400, a depletion layer (not shown) expands in the n-type semiconductor layer 401a, thereby becoming a high-voltage SBD. In addition, when a forward bias is applied, electrons flow from the ohmic electrode 403 to the Schottky electrode 402. Therefore, the SBD of the present invention is excellent for high voltage / large current, has a fast switching speed, and is excellent in voltage resistance / reliability.
[0093] Figure 4 HEMT 500 is an example of a high electron mobility transistor (HEMT). HEMT 500 includes an n-type semiconductor layer 501 with a wide energy bandgap, an n-type semiconductor layer 502 with a narrow energy bandgap, an n+ type semiconductor layer 503, a semi-insulator layer 504, a buffer layer 505, a gate electrode 506, a source electrode 507, and a drain electrode 508.
[0094] Figure 5 The MOSFET 600 is an example of a metal oxide semiconductor field effect transistor (MOSFET). The MOSFET 600 includes an n-type semiconductor layer 601 , n+ type semiconductor layers 602 and 603 , a gate insulating film 604 , a gate electrode 605 , a source electrode 606 , and a drain electrode 607 .
[0095] Figure 6 The IGBT 700 is an example of an insulated gate bipolar transistor (IGBT). The IGBT 700 includes an n-type semiconductor layer 701 , an n-type semiconductor layer 702 , an n+ type semiconductor layer 703 , a p-type semiconductor layer 704 , a gate insulating film 705 , a gate electrode 706 , an emitter 707 , and a collector 708 .
[0096] Figure 7The LED 800 is an example of a light emitting diode (LED). The LED 800 includes a first electrode 801 , an n-type semiconductor layer 802 , a light emitting layer 803 , a p-type semiconductor layer 804 , a light-transmitting electrode 805 , and a second electrode 806 .
[0097] As the material of the light-transmitting electrode 805, conductive materials containing oxides of indium or titanium can be listed. More specifically, for example, In2O3, ZnO, SnO2, Ga2O3, TiO2, CeO2, or a mixed crystal of two or more of these components or a material doped in these components can be listed. By setting these materials using a known method such as sputtering, the light-transmitting electrode 805 can be formed. In addition, after the light-transmitting electrode 805 is formed, thermal annealing for the purpose of making the light-transmitting electrode 805 transparent can also be performed.
[0098] As materials for the first electrode 801 and the second electrode 806, for example, metals such as aluminum, molybdenum, cobalt, zirconium, tin, niobium, iron, chromium, tantalum, titanium, gold, platinum, vanadium, manganese, nickel, copper, hafnium, tungsten, iridium, zinc, indium, palladium, neodymium or silver or alloys of these metals, metal oxide conductive films such as tin oxide, zinc oxide, rhenium oxide, indium oxide, indium tin oxide (ITO), zinc indium oxide (IZO), organic conductive compounds such as polyaniline, polythiophene or polypyrrole, or mixtures of these components, etc. The film forming method of the electrode is not particularly limited, and can be formed by a method appropriately selected from wet methods such as printing, spraying, and coating, physical methods such as vacuum evaporation, sputtering, and ion plating, and chemical methods such as CVD and plasma CVD, etc., in consideration of the compatibility with the above materials.
[0099] Then, refer to Figure 8 right Figure 1 An example of the method for producing the laminated body in the present invention described in is described below, but the present invention is not limited thereto.
[0100] Figure 8An example of an apparatus used in the method for manufacturing a laminate of the present invention is shown. In the method for manufacturing a laminate of the present invention, an atomizing CVD apparatus 300 is used. First, as a raw material solution, a first metal oxide precursor 312a and a second metal oxide precursor 312b are respectively contained in atomizers 302a and 302b, and atomized (also referred to as "misting") using a known method to form a mist. As the first metal oxide precursor 312a and the second metal oxide precursor 312b, for example, a gallium solution obtained by dissolving an organic metal complex of a metal (such as an acetylacetone complex, etc.) or metal gallium in an acid solution or an aqueous solution of a halide (such as a fluoride, chloride, bromide or iodide, etc.) can be cited. The metal is not limited as long as it can form a corundum-type structure as a metal oxide crystal, and for example, aluminum, titanium, vanadium, chromium, iron, gallium, rhodium, indium, and iridium can be cited. In addition, the metals contained in the first metal oxide precursor 312 a and the second metal oxide precursor 312 b may be the same or different.
[0101] The content of the metal in the raw material solution is not particularly limited and can be appropriately set according to the purpose or specification, but is preferably 0.001 mol % to 50 mol %, and more preferably 0.01 mol % to 5 mol %.
[0102] When at least a part of the stack is given conductivity, doping may be performed. The impurity raw material at this time is not particularly limited. For example, when the metal contains at least gallium, a complex or compound containing silicon, germanium, tin, magnesium, or copper may be preferably used. In particular, when n-type conductivity is given, tin halide is preferably used. 0.1 to 20 at%, preferably 1 to 10 at%, of the impurity raw material may be mixed in the raw material solution for use.
[0103] The solvent of the raw material solution is not particularly limited, and may be an inorganic solvent such as water, an organic solvent such as alcohol, or a mixed solvent of an inorganic solvent and an organic solvent. Water is preferably used.
[0104] Furthermore, the mist CVD apparatus 300 includes a supply device for a carrier gas 301. The carrier gas 301 is mixed with the misted raw material solution (metal oxide precursor) formed in the misters 302a and 302b, and is transported to the film forming chamber 309.
[0105] exist Figure 8 In the example shown, the atomizer 302b and the film forming chamber 309 are connected by the delivery tube 306, and the delivery tube (silicon addition tube) 303 from the atomizer 302a merges in the middle of the delivery tube 306, but the delivery tube (silicon addition tube) 303 and the delivery tube 306 may be independently connected to the film forming chamber 309. In addition, the delivery tube (silicon addition tube) 303 will be described in detail later.
[0106] The carrier gas 301 is not particularly limited. In addition to air, oxygen, and ozone, for example, an inert gas such as nitrogen or argon, or a reducing gas such as hydrogen or a forming gas is preferably used. The type of carrier gas can be one or more. The flow rate of the carrier gas can be appropriately set according to the size of the substrate or the size of the film forming chamber, and can be set to about 0.01 to 40 L / min.
[0107] In addition, although not shown in the figure, a dilution gas may be added to adjust the ratio of the atomized raw material to the carrier gas. The flow rate of the dilution gas only needs to be appropriately set, and may be set to 0.1 to 10 times / minute of the carrier gas. For example, the dilution gas may be supplied to the downstream side of the atomizers 302a and 302b. The dilution gas may be the same gas as the carrier gas, or a gas different from the carrier gas.
[0108] The structure of the film-forming chamber 309 is not particularly limited, and metals such as aluminum or stainless steel can be used. When the film is formed at a higher temperature than the heat-resistant temperature of these metals, quartz or silicon carbide can be used. A heating device 310 for heating the crystal substrate 307 can be provided inside or outside the film-forming chamber 309.
[0109] In addition, the crystal substrate 307 may be placed on a susceptor 308 provided in a film forming chamber 309 .
[0110] (Step of forming a first mixed gas)
[0111] First, a first mixed gas 313 is formed, which is a mixture of a carrier gas 301, an atomized first metal oxide precursor formed by an atomizer 302a, and silicon. Figure 8 In the example shown, silicon is added during the transportation of the carrier gas 301 and the atomized first metal oxide precursor to the crystal substrate 307 placed in the film forming chamber 309 to form the first mixed gas 313. As a method of adding silicon during transportation, for the sake of simplicity, it is preferable to add silicon by passing it through a transportation tube (silicon addition tube) 303. As the transportation tube (silicon addition tube) 303, for example, a silicone resin tube containing silicone resin as a main component can be used, for example, methyl silicone rubber, vinyl-methyl silicone rubber, phenyl-methyl silicone rubber, etc. are preferably used.
[0112] In addition, instead of using the delivery tube (silicon addition tube) 303 to add silicon, a method such as pre-adding silicon raw material to the carrier gas 301 or adding silicon raw material to the atomizer 302a can be used. However, if silicon is added only through the delivery tube (silicon addition tube) 303 in the above manner, it is very easy to form the first mixed gas.
[0113] (Step of forming an intermediate layer)
[0114] The first mixed gas 313 formed in the above manner is transported to the crystal substrate 307 placed on the base 308 in the film forming chamber 309 and heated by the heating device 310, thereby forming an intermediate layer of a crystalline region of a crystalline phase composed of a corundum-type structure with the first metal oxide as the main component and an amorphous region of an amorphous phase.
[0115] Since silicon compounds, mainly siloxanes from silicone resins, are mixed into the first mixed gas 313 during the transportation process in the transportation tube (silicon addition tube) 303, it is believed that when the intermediate layer is formed, the silicon will form silicon oxide inside the intermediate layer, which will disrupt the partial crystal structure of, for example, gallium oxide, and thus partially form an amorphous region.
[0116] The supply of the first mixed gas 313 to the film forming chamber 309 is appropriately regulated by opening and closing the valve 304, and the supply is stopped after the intermediate layer having a desired film thickness is formed.
[0117] The supply amount of the first mixed gas 313 can be changed during the formation of the intermediate layer. This makes it easy to control the ratio of the crystalline region in the intermediate layer and the thickness of the intermediate layer, thereby improving productivity and producing the laminate at low cost.
[0118] In addition, Figure 8 In the figure, the valve 304 is arranged on the upstream side of the atomizer 302a, but the invention is not limited thereto and the valve 304 may also be arranged on the downstream side of the atomizer 302a.
[0119] (Step of Forming Second Mixed Gas)
[0120] Furthermore, a second mixed gas 323 is formed by mixing the atomized second metal precursor (mist) formed in the atomizer 302b and the carrier gas 301. The second mixed gas 323 is formed in the same manner as the first mixed gas except that silicon is not added.
[0121] (Step of forming a crystal layer on an intermediate layer)
[0122] The second mixed gas 323 formed in this manner is supplied to the crystal substrate 307 placed on the susceptor 308 and heated in the film forming chamber 309 , thereby forming a crystal layer having a corundum type structure mainly composed of the second metal oxide on the intermediate layer.
[0123] The second mixed gas 323 introduced into the film formation chamber 309 reacts on the crystal substrate 307 heated by the heat source 310 in the film formation chamber 309 to form a crystal layer.
[0124] The temperature of the crystal substrate 307 is appropriately set according to the raw material used or the target formation object, but when forming the intermediate layer, it can be 350° C. to 600° C., and more preferably 400° C. to 500° C. By setting the temperature in the above range, the intermediate layer containing a mixture of a crystalline region and an amorphous region can be formed more stably.
[0125] Furthermore, for example, when forming an α-phase gallium oxide crystal layer on the intermediate layer, the temperature is preferably 380° C. to 900° C. By setting the temperature range as above, an α-phase gallium oxide crystal layer can be formed more stably than a β-phase one.
[0126] The film formation may be carried out under any of atmospheric pressure, increased pressure, and reduced pressure. However, it is preferably carried out under atmospheric pressure from the viewpoint of equipment cost and productivity.
[0127] In addition, the film thickness can be set by adjusting the film formation time or the carrier gas flow rate.
[0128] In addition, when forming the intermediate layer, the mixed gas supplied to the film forming chamber 309 may be only the first mixed gas 313, or both the first mixed gas 313 and the second mixed gas 323. When the first mixed gas 313 and the second mixed gas 323 are supplied at the same time, for example, it is preferable to set the total flow rate of the carrier gas flowing to the atomizers 302a and 302b within the above-mentioned flow rate range. Figure 8 The middle valves 304 and 305 are arranged on the upstream side of the atomizers 302a and 302b, but may also be arranged on the downstream side of the atomizers 302a and 302b.
[0129] Example
[0130] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to the Examples.
[0131] (Example)
[0132] Use with Figure 8 The same atomization CVD apparatus was used to produce the laminated body.
[0133] Two sprayers (sprayer A and sprayer B) as atomizers and a quartz film-forming chamber were prepared. The film-forming chamber and sprayer A were connected by a quartz tube, and sprayer B was connected to the quartz tube connected to sprayer A in front of the film-forming chamber via a silicone resin tube.
[0134] Next, 34% hydrochloric acid was added to a 0.02 mol / L aqueous solution of gallium acetylacetonate at a volume ratio of 1%, and stirred for 60 minutes using a stirrer to obtain a precursor. The precursor was filled in two sprayers (sprayer A and sprayer B), respectively.
[0135] Next, a c-plane sapphire substrate having a thickness of 0.45 mm was placed on a susceptor provided in a film deposition chamber, and heated so that the substrate temperature reached 450°C.
[0136] Next, ultrasonic vibrations were propagated to the precursors in the sprayers A and B through water using a 2.4 MHz ultrasonic oscillator, thereby atomizing the precursors.
[0137] Next, nitrogen gas was added to the sprayer B at a flow rate of 5 L / min, and a mixed gas of the atomized precursor and nitrogen gas was supplied to the film forming chamber for 5 minutes to form an intermediate layer with a film thickness of about 70 nm. Then, the supply of nitrogen gas to the sprayer B was stopped, and the supply of the mixed gas to the film forming chamber was stopped.
[0138] Next, nitrogen gas was added to the sprayer A at a flow rate of 5 L / min, and a mixed gas of mist and nitrogen gas was supplied to the film forming chamber for 30 minutes to form a crystal layer with a film thickness of about 300 nm. Then, the supply of nitrogen gas to the sprayer A was stopped, and the supply of the mixed gas to the film forming chamber was stopped.
[0139] Next, heating of the substrate is stopped, and after cooling to near room temperature, the substrate is taken out from the film formation chamber.
[0140] The crystal layer of the produced laminate showed a peak at 2θ=40.3° in X-ray diffraction measurement, thereby confirming that it was α-phase Ga2O3.
[0141] Then, the produced laminate was analyzed by transmission electron microscopy (TEM) and energy dispersive X-ray analysis (EDX).
[0142] (Comparative Example)
[0143] The sprayer B and the silicone resin tube were removed from the apparatus used in the example, and the crystal layer was formed into a film.
[0144] First, the same precursor as that used in the example was filled in the sprayer A.
[0145] Next, a c-plane sapphire substrate having a thickness of 0.45 mm was placed on a susceptor provided in a film deposition chamber, and heated so that the substrate temperature reached 450°C.
[0146] Next, ultrasonic vibrations were propagated to the precursor in the sprayer A through water using a 2.4 MHz ultrasonic oscillator, thereby atomizing the precursor.
[0147] Next, nitrogen gas was added to the sprayer A at a flow rate of 5 L / min, and a mixed gas of mist and nitrogen gas was supplied to the film forming chamber for 35 minutes to form a crystal layer. Then, the supply of nitrogen gas to the sprayer A and the supply of the mixed gas to the film forming chamber were stopped.
[0148] Next, heating of the substrate is stopped, and after cooling to near room temperature, the substrate is taken out from the film formation chamber.
[0149] The crystal layer of the produced laminate showed a peak at 2θ=40.3° in X-ray diffraction measurement, thereby confirming that it was α-phase Ga2O3.
[0150] Then, the produced laminate was analyzed by transmission electron microscopy (TEM) and the silicon concentration in the laminate was analyzed by EDX.
[0151] Fig. 9 A cross-sectional TEM image of a laminate prepared in the example is shown. Fig.10 The cross-sectional TEM image of the laminate prepared in the comparative example is shown. Fig. 9 In the embodiment shown, an intermediate layer containing columnar crystalline regions is formed on a substrate. In the intermediate layer in the cross-sectional TEM image, the columnar portion that appears darker is the crystalline region. Image analysis of TEM images at multiple locations using the same sample revealed that the proportion of the crystalline region in the intermediate layer is approximately 9.5%. Fig.10 In the comparative example shown, no intermediate layer was formed.
[0152] Furthermore, looking at the crystal layer, it can be seen that in the embodiment, in the crystal layer on the intermediate layer, large crystal grains (whiter looking parts) are formed which grow using the columnar crystals of the intermediate layer as seeds. Fig.10 Compared with the crystal layer of the comparative example shown, the crystal defects observed as a black contrast extending in the film growth direction are significantly reduced.
[0153] Fig.11 Shows Fig. 9 , Fig.10 The concentration distribution of silicon atoms in the field of view. Fig. 9 ), a maximum of about 2.0 at% silicon was detected in a region about 70 nm from the substrate surface in contact with the intermediate layer. On the other hand, the silicon concentration in the crystal layer of the embodiment and the crystal layer of the comparative example was at the noise level and was not detected.
[0154] From the above results, it is understood that according to the present invention, a high-quality crystal layer (crystal film) with fewer defects than in the prior art can be obtained.
[0155] Furthermore, in the present invention, since the intermediate layer and the crystal layer are formed by one device, a high-quality crystal layer (crystal film) with low defects and high productivity can be obtained at extremely low cost, compared with the conventional ELO method which uses other devices for forming an ELO growth mask or requires a photolithography process. Furthermore, as described above, since no other devices are required, the possibility of contamination of the crystal substrate is also reduced.
[0156] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any technical solution having substantially the same configuration and having the same function and effect as the technical concept described in the claims of the present invention is included in the technical scope of the present invention.
Claims
1. A laminate, characterized in that: The laminate has: Crystal substrate; an intermediate layer formed on the main surface of the crystal substrate and including a crystalline region of a crystalline phase and an amorphous region of an amorphous phase mixed together, wherein the crystalline region of the crystalline phase has a first metal oxide as a main component and is composed of a corundum type structure; and a crystal layer of a corundum type structure having a second metal oxide as a main component formed on the intermediate layer, The intermediate layer further contains silicon.
2. The laminate according to claim 1, characterized in that The crystalline region is an epitaxial growth layer starting from the crystal plane of the crystalline substrate.
3. The laminate according to claim 1, characterized in that In any cross section of the intermediate layer perpendicular to the main surface of the crystal substrate, the ratio of the crystal region contained in the intermediate layer is 1% or more.
4. The laminate according to claim 1, wherein: In any cross section of the intermediate layer perpendicular to the main surface of the crystal substrate, the ratio of the crystal region contained in the intermediate layer is 4% to 25%.
5. The laminate according to claim 1, wherein: The intermediate layer has a thickness of 1 nm or more.
6. The laminate according to claim 1, characterized in that The intermediate layer has a thickness of 10 nm or more.
7. The laminate according to claim 1, wherein: The first metal oxide contains an oxide of any one of aluminum, titanium, vanadium, chromium, iron, gallium, rhodium, indium, and iridium as a main component.
8. The laminate according to claim 1, wherein: The second metal oxide contains an oxide of any one of aluminum, titanium, vanadium, chromium, iron, gallium, rhodium, indium, and iridium as a main component.
9. The laminate according to claim 1, characterized in that The concentration of the silicon contained in the intermediate layer is 0.5 at % or more.
10. The laminate according to claim 1, wherein: The concentration of the silicon contained in the intermediate layer is greater than or equal to 1 at % and less than or equal to 10 at %.
11. The laminate according to any one of claims 1 to 10, characterized in that A stress relaxation layer is further provided between the crystal substrate and the intermediate layer. 12 . A semiconductor device comprising at least a semiconductor layer and an electrode, wherein the semiconductor device comprises at least a part of the stacked body according to claim 1 as the semiconductor layer.
13. A method for producing a laminate, characterized in that: The following steps are involved: The step of forming a first mixed gas containing an atomized first metal oxide precursor, a carrier gas, and silicon; The step of supplying the first mixed gas onto the heated crystal substrate to form an intermediate layer in which a crystalline region of a crystalline phase and an amorphous region of an amorphous phase are mixed, wherein the crystalline region of the crystalline phase has a first metal oxide as a main component and is composed of a corundum type structure; forming a second mixed gas containing an atomized second metal oxide precursor and a carrier gas; and The step of supplying the second mixed gas onto the heated crystal substrate to form a crystal layer having a corundum type structure having a second metal oxide as a main component on the intermediate layer.
14. The method for producing a laminate according to claim 13, wherein: In the step of forming the first mixed gas, the silicon is added while the atomized first metal oxide precursor and the carrier gas are being transported onto the crystal substrate.
15. The method for producing a laminate according to claim 14, wherein: The silicon is added by conveying the atomized first metal oxide precursor and the carrier gas through a tube made of a silicone resin.
16. The method for producing a laminate according to any one of claims 13 to 15, characterized in that: In the step of forming the intermediate layer, a supply amount of the first mixed gas is changed.
Citation Information
Patent Citations
Multiinput logical circuit
JP1982093732A
Crystalline laminate structure and method for manufacturing the same
JP2016100592A
Semiconductor device and manufacturing method for same, crystal, and manufacturing method for same
US20160149005A1